Conservative non-surgical management of an infected radicular cyst - Harleen Narula; Bhoomika Ahuja; Ramakrishna Yeluri; Sudhindra Baliga; Autar Krishen Munshi (Wolters Kluwer Medknow Publications, 2011)
The radicular cyst arises from epithelial remnants stimulated to proliferate by an inflammatory process originating from pulpal necrosis of a non-vital tooth. Radiographically, the classical description of the lesion is a round or oval, well-circumscribed radiolucent image involving the apex of the tooth. Radicular cyst is usually sterile unless it is secondarily infected. This article presents a successful case of conservative non-surgical management of an infected radicular cyst associated with an immature permanent mandibular second molar (47) in a 14-year-old child.